American poetry: the divided tradition - Dolan, Paul (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1990)
What is American poetry? This paper is a history of the various answers poets have given to that question. They include Whitman's creation of a new form for poetry, one to replace those inherited from England. This new poetry was as radical politically as it was poetically —it was created to include those that other poetic forms had left out. Frost, on the other hand, adapted British verse forms to an American scene and American verse. The contradictory nature of America's response to Europe has shaped the divided tradition of American poetry.